2021
DOI: 10.1002/cplu.202100103
|View full text |Cite
|
Sign up to set email alerts
|

Subphthalocyanine‐Diketopyrrolopyrrole Conjugates: 3D Star‐Shaped Systems as Non‐Fullerene Acceptors in Polymer Solar Cells with High Open‐Circuit Voltage

Abstract: Dedicated to Prof. Dr. Nazario Martín on the occasion of his 65th birthdayFour star-shaped electron acceptors (C 1 -OPh, C 3 -OPh, C 1 -Cl and C 3 -Cl) based on a subphthalocyanine core bearing three diketopyrrolopyrrole wings linked by an acetylene bridge have been synthesized. These derivatives feature two different axial substituents (i. e., 4-tert-butylphenoxy (OPh) or chlorine (Cl)) and for each of them, both the C 1 and the C 3 regioisomers have been investigated. The four compounds exhibit a broad absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…For instance, PCEs up to 4.6% and 3.17% have been reported employing SubPcs peripherally functionalized with -(3-oxo-2,3-dihydroinden-1-3-ylidene) maleonitriles 116 and diketopyrrolopyrrole groups, respectively. 450 2.7.1.3 Tandem solar cells. Tandem configuration (TSCs; Fig.…”
Section: Subphthalocyanines As Donor Materialmentioning
confidence: 99%
“…For instance, PCEs up to 4.6% and 3.17% have been reported employing SubPcs peripherally functionalized with -(3-oxo-2,3-dihydroinden-1-3-ylidene) maleonitriles 116 and diketopyrrolopyrrole groups, respectively. 450 2.7.1.3 Tandem solar cells. Tandem configuration (TSCs; Fig.…”
Section: Subphthalocyanines As Donor Materialmentioning
confidence: 99%
“…Therefore, an electrochemical energy gap of 1.82 eV is calculated. From these results, the LUMO level is estimated to be −4.03 eV, which is comparable to other high performing SubPc acceptors (−4.25 eV) or PC 61 BM (−4.26 V) . Further insight into these redox properties was obtained by inspection of the DFT calculated frontier molecular orbitals.…”
mentioning
confidence: 61%
“…Among them, imide-fused porphyrinoids are particularly exciting due to additional properties such as strong Vis−NIR absorption, tunable energy levels, and multiple reversible reductions . In this context, subphthalocyanines (SubPcs; Figure ), which are cone-shape aromatic dyes composed of three aza-bridged diiminoisoindole units and a central boron atom, have demonstrated an outstanding potential in bulk-heterojunction (BHJ) organic solar cells (OSCs) . Hereby, Huang et al reported a perylene bisimide-fused SubPc derivative that holds the power conversion efficiency (PCE) record of 7.5% for solution-processed SubPc-based OSCs in combination with donor polymer PM6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts were executed including the optimal reaction conditions above, but the mixed cyclotrimerizations with (10), (11), and (12) each resulted in mixtures primarily containing the C 3v -symmetric BsubPc and recovering most of the starting material (4). These results suggested a substantial lack in reactivity of (4) with this series of o-dinitriles (Tables S6−S8).…”
Section: Probing the Lewis Basicity Of O-dinitrilesmentioning
confidence: 99%